They built Utopia : the Jesuit missions in Paraguay, 1610-1768 - Reiter, Frederick J. (Potomac, Md., U.S.A. : Scripta Humanistica, 1995)
"Relates story of Jesuit ouster from Spain and Paraguay beginning with state demands for indigenous soldiers in 1734, moving through Jesuit resistance to the border treaties between Spain and Portugal and the growing anti- Jesuit movement in the court of Charles III. Author attempts to liven up the story by creating dramatic conversations, but work is based on research in primary and secondary sources"--Handbook of Latin American Studies, v. 58.
Introduction -- Part I. The investigation - 1. The state within the state - 2. The view from Madrid - 3. Beginnings - 4. The enemies - 5. Ecclesiastic and fiscal problems - 6. The communal system - 7. The daily life. - 8. A Garden of Christianity - 9. Language - militia - jesuit hierarchy - 10. The royal approval -- Part II. The border treaty between Spain and Portugal - 1. The Portuguese connection - 2. Seven of the missions : Sold Out -- 3. Don Jose de Carvajal, the Minister - 4. The King's Commissar - 5. The Padre Comisario General - 6. The indians resist -- 7. The Guarani War, first campaign -- 8. Madrid accuses the Jesuits - 9. Don Ricardo Wall, the new minister - 10. The Guarani War, second campaign - 11. Don Pedro de Ceballos, the new governor of Buenos Aires - 12. The Portuguese double cross - 13. Ceballos and the Jesuits - 14. The Padres' Loyalty affirmed - 15. Carvalho's final attack - 16. The expulsion from Portugal -- Part III: The expulsion from Spain - 1. The New King, Carlos III - 2. Turnabout in Paraguay - 3. The expulsion from France - 4. Rebuilding the missions - 5. Conspiracy at the court in Madrid - 6. Riots in Madrid - "El Motin" - 7. Count Aranda takes charge - 8. Secret investigation and expulsion decree - 9. Aranda's private problem - 10. Expulsion from Spain-11. Expulsion from Paraguay - Bibliography - Appendices - Index.
Includes bibliographical references (p. 361-381) and indexes.
Keywords: Jesuits -- Missions -- Paraguay -- History; Catholic Church -- Missions -- Paraguay -- History; Guarani Indians -- Missions -- Paraguay -- History; Indians of South America -- Missions -- Paraguay -- History; Utopias -- Religious aspects -- Christianity; Utopias -- Paraguay; Electronic books